Factors influencing first-time homebuyers' purchase decision - Tay, Xue Xuan (2024)
The focal areas of this study include Financial Factors (FF), Property Location (PL), Corporate Image (CI), and Property Attributes (PA), which are deemed crucial in the current challenging economic landscape where numerous developers operate in the market. The objective of this study is to offer valuable perspectives for developers, marketers, investors, property purchasers, and prospective researchers, aiding in understanding the determinants of first-time homebuyer purchase decisions in the residential property market of Klang Valley. To achieve this objective, data was gathered through a survey questionnaire targeting first-time homebuyers in the Klang Valley. A total of 171 questionnaires were distributed online to individuals intending to purchase residential properties in the mentioned area. The collected data was analysed using Statistical Package for Social Sciences (SPSS) version 23.0 and Smart PLS 4.0. Based on the findings, several recommendations are provided, offering practical suggestions for stakeholders in the industry, and indicating avenues for further research in this domain.